A Phase 2, Double-Blind, Randomized, Dose-Ranging Trial Of Reldesemtiv In Patients With ALS. Issue 3 (3rd April 2021) - Shefner, Jeremy M.; Andrews, Jinsy A.; Genge, Angela; Jackson, Carlayne; Lechtzin, Noah; Miller, Timothy M.; Cockroft, Bettina M.; Meng, Lisa; Wei, Jenny; Wolff, Andrew A.; Malik, Fady I.; Bodkin, Cynthia; et al.
Abstract: Objective: To evaluate safety, dose response, and preliminary efficacy of reldesemtiv over 12 weeks in patients with amyotrophic lateral sclerosis (ALS). Methods: Patients (≤2 years since diagnosis) with slow upright vital capacity (SVC) of ≥60% were randomized 1:1:1:1 to reldesemtiv 150, 300, or 450 mg twice daily (bid) or placebo; active treatment was 12 weeks with 4-week follow-up. Primary endpoint was change in percent predicted SVC at 12 weeks; secondary measures included ALS Functional Rating Scale-Revised (ALSFRS-R) and muscle strength mega-score. Results: Patients ( N  = 458) were enrolled; 85% completed 12-week treatment. The primary analysis failed to reach statistical significance ( p  = 0.11); secondary endpoints showed no statistically significant effects (ALSFRS-R, p  = 0.09; muscle strength mega-score, p  = 0.31). Post hoc analyses pooling all active reldesemtiv -treated patients compared against placebo showed trends toward benefit in all endpoints (progression rate for SVC, ALSFRS-R, and muscle strength mega-score (nominal p values of 0.10, 0.01 and 0.20 respectively)). Reldesemtiv was well tolerated, with nausea and fatigue being the most common side effects. A dose-dependent decrease in estimated glomerular filtration rate was noted, and transaminase elevations were seen in approximately 5% of patients. Both hepatic and renal abnormalities trended toward resolution after study drug discontinuation. Conclusions: Although the primary efficacy analysis did not demonstrate statistical significance, there were trends favoring reldesemtiv for all three endpoints, with effect sizes generally regarded as clinically important. Tolerability was good; modest hepatic and renal abnormalities were reversible. The impact of reldesemtiv on patients with ALS should be assessed in a pivotal Phase 3 trial. (ClinicalTrials.gov Identifier: NCT03160898)